Analisis Evaluasi Kualitas Pelayanan di K3 Mart Graha Pena Surabaya: Pengalaman Konsumen - Annisa Septi Amaliyah; Melinda Rosilawati; Eli Masnawati (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
K3 Mart is a minimarket that markets various kinds of Korean products and from other countries as well as MSME products with a lifestyle theme. The products marketed at the minimarket are halal products. This research was conducted with the aim of finding out the quality of service provided by employee staff to consumers based on the consumer's experience after visiting. This research is qualitative research with a focus on analyzing consumer experiences regarding service quality. This research uses descriptive research. The research method used is a qualitative method with interview and observation data collection techniques. The indicators used in this research are physical evidence, reliability, empathy, responsiveness and assurance. The research results show that the five indicators have been well implicated by business owners and staff employees. Even though it is considered quite good, the business owner and staff are still trying to improve the quality of service at K3 Mart Graha Pena.